Superwettable nanodendritic gold substrates for direct miRNA SERS detection - Song, Yongchao; Xu, Tailin; Xu, Li-Ping; Zhang, Xueji (Nanoscale, 2018)
By combining a superwettable interface with a nanodendritic gold structure, we have fabricated a superwettable nanodendritic gold substrate for direct SERS detection of multiple concentrations of miRNAs. The nanodendritic gold substrate provides numerous hotspots for Raman signal enhancement, and the superwettable interface ensures the immobilization of droplets in superhydrophilic microwells, which hold great potentials for applications in disease diagnostics.